2018
DOI: 10.1002/pon.4672
|View full text |Cite
|
Sign up to set email alerts
|

Quality of partner support moderates positive affect in patients with cancer

Abstract: The findings suggest that only when the quality of support is high does social support have a positive impact on patients' positive affect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…Besides professional care, family communication and social support also play an important role in preventing suicides and suicide attempts. 1,51,52 There were some limitations in our study. Besides pathological factors, suicide was affected by psychological and social factors which could not be provided by the SEER database.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Besides professional care, family communication and social support also play an important role in preventing suicides and suicide attempts. 1,51,52 There were some limitations in our study. Besides pathological factors, suicide was affected by psychological and social factors which could not be provided by the SEER database.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, the efforts for decreasing suicide need coordination and collaboration, including medical workers, family members even the whole society. Besides professional care, family communication and social support also play an important role in preventing suicides and suicide attempts …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that low levels of partner support are associated with higher levels of antenatal anxiety and depression during pregnancy (Cheng et al, ) and that low levels of shared communication, relationship satisfaction and emotional and instrumental support increase the risk of developing depression (Pilkington, Milne, Cairns, Lewis, & Whelan, ). Women with cancer who were in an unsupportive relationship with their partners had higher risk of developing anxiety symptoms, manifested lower levels of positive affect and had lower levels of reported quality of life (Borstelmann et al, ; Gustavsson‐Lilius, Julkunen, & Hietanen, ; Kaliampos & Roussi, ).…”
Section: Discussionmentioning
confidence: 99%
“…This attention may be effective in prevention if a high-risk group can be identified, as it was reported in an Australian series [ 32 ]. In addition to the importance of patients’ understanding of the cancer diagnosis and all treatment modalities, promotion of family communication combined with encouragement of self-determination and participation in treatment can mitigate the suicide risk [ 32 34 ].…”
Section: Discussionmentioning
confidence: 99%